C3b/iC3b Deposition on Streptococcus pneumoniae Is Not Affected by HIV Infection - Hyams, Catherine (Public Library of Science, 2010)
Streptococcus pneumoniae is a common cause of infection in both HIV positive patients and those with complement deficiencies. We hypothesised that HIV positive individuals might exhibit reduced opsonisation of pneumococcus with complement due to reduced levels of S. pneumoniae specific IgG. We discovered no difference in C3 deposition on S. pneumoniae between HIV positive or negative individuals, and furthermore C3 deposition remained unchanged as HIV progressed towards AIDS. We found no correlation between C3 deposition on S. pneumoniae and CD4 cell count in HIV infected individuals. Hence we have demonstrated no failure of complement immunity in HIV positive patients.